Psychological Distance Toward Air Pollution and Purchase Intention for New Energy Vehicles: An Investigation in China - Liu, Wenlong; Zeng, Lele; Wang, Qunwei (Frontiers in Psychology, 2021)
Air pollution in China has been drawing considerable attention in recent years. The emergence of new energy vehicles (NEVs) provides hope to reduce air pollutant emission. However, consumers’ recognition and acceptance of NEVs remain at the early stage. This study aims to explore how consumers’ environmental concern influences their NEV purchase intention. Specifically, this study conducted an online survey and an experiment to address the following issues: (1) how consumers’ psychological distance (PD) toward air pollution influences their purchase intention for NEVs, and does their risk perception of the consequences of air pollution mediate this influence; (2) whether consumers’ perceived price level of NEVs plays a moderating role in the relationship between risk perception and purchase intention; and (3) whether the construal level of stimulus can be manipulated to influence consumers’ PD toward air pollution to increase their purchase intention for NEVs. The results of study 1, based on a total of 293 valid samples, show that consumers’ PD toward air pollution significantly affects their purchase intention for NEVs, and risk perception of the consequences of air pollution plays a considerable mediating role. Meanwhile, consumers’ perceived price level of NEVs has a significant negative moderating effect on the relationship between risk perception and purchase intention. The results of study 2, based on an online experiment, show that the construal level of stimulus can influence consumers’ PD toward air pollution, which in turn affects their purchase intention for NEVs. The findings of this research have implications for businesses’ promotional strategies and governments’ policies. For instance, low-construal-level promotional materials can be developed to arouse consumers’ environmental concern, thereby facilitating their eco-friendly consumption behavior. Governmental financial assistance and other policies can also increase consumers’ willingness to purchase NEVs.